Quadrimalleolar ankle fracture with syndesmosis disruption—a minimally invasive approach with arthroscopic repair of the anterior-inferior tibiofibular ligament (AITFL); a case report - Ming Hong Chau, M.B.Ch.B., F.H.K.C.O.S., F.H.K.A.M. (Orthopaedic Surgery), F.R.C.S.Ed. (Orth.), M.R.C.S.Ed.; Ka Ki Stephanie Liu, M.B.B.S., F.H.K.C.O.S., F.H.K.A.M. (Orthopaedic Surgery), F.R.C.S.Ed. (Orth.), M.R.C.S.Ed. (Trauma Case Reports)
We describe the case of a 61-year-old Chinese female who presented with a closed quadrimalleolar ankle fracture subluxation with avulsion fracture of anterolateral tibial rim along with disruption of the syndesmosis. The fibula fracture was fixed under minimally invasive approach with a fibula nail and the anterior-inferior tibiofibular ligament (AITFL) was repaired arthroscopically, together with fixation of the medial malleolus fracture. This is the first reported case in which a similar technique was used. At the 3-month follow-up, the fracture has healed completely with good cosmetic and clinical outcome.